Hans den Besten, Frans Hinskens & Jerzy Koch (reds) Afrikaans: Een drieluik - Conradie, Jac (Department of Dutch and South African Studies, Faculty of English, 2010)
Recenzja: Hans den Besten, Frans Hinskens & Jerzy Koch (reds) Afrikaans: Een drieluik Amsterdam: Stichting Neerlandistiek VU Münster: Nodus Publikationen, 2009 255 pp. ISBN/EAN: 978-90-8880-010-8, 978-3-89323-758-6